Thermal Decomposition of Pellets from a Mixture of Peat and Bark Waste - Aleksey P. Terekhin; Pavel A. Maryandyshev; Irina I. Golovanova; Anton A. Gromov (Лесной журнал)
There are large peat deposits in the Arkhangelsk Region. According to the balance sheet data, there are 626 deposits, each of which has an area exceeding 10 ha. At the same time, the Arkhangelsk Region faces the problem of efficient energy utilization of secondary energy resources, such as wood waste and bark, generated at timber industry enterprises. Thermal analysis of pellets from a mixture of peat (80 %) and bark waste from pulp and paper production (20 %) has been performed on a synchronous thermal analyzer in an argon and air environment in the temperature range of 30–700 °С. Peat has been collected in the Mezensky District of the Arkhangelsk Region, and samples of bark waste have been collected from the bark feed line to the E-75-3.9-440 DFT and KM75-40M fluidized bed boiler units installed at TPP-3 of Arkhangelsk Pulp and Paper Mill. The pellets have been obtained in a pellet-press. The elemental composition of pellets has been studied using a spectrometer. The main ash- and slag-forming elements in the samples are silicon, aluminum, calcium and iron. The thermal analysis of pellets has been carried out on a synchronous thermal analyzer in an argon and air medium with a flow rate of 20 cm3/min. To observe the drying and thermal transformations of pellets, the curves of the decrease in mass and speed of this process in the studied samples of fuel pellets have been used. It has been shown that the release of volatile substances has occurred at temperatures from 170 to 430 °C. The resulting pellets are high-calorie and low-ash biofuel. The results of the research can be applied for theoretical substantiation of the production of fuels with high combustion heat and mechanical strength in order to increase the role of local biomass in the energy sector of the Arkhangelsk Region.